Room-temperature growth of fluorapatite/CaCO3 heterogeneous structured composites inspired by human tooth. Issue 18 (8th April 2022) - Li, Yidi; Ping, Hang; Lei, Liwen; Xie, Jingjing; Zou, Zhaoyong; Wang, Weimin; Wang, Kun; Fu, Zhengyi
Abstract : Fluorapatite/CaCO3 thin films were synthesized by mimicking their biogenic counterparts found in teeth using a biomimetic mineralization method. The synthetic heterostructure composites combine well and exhibit excellent mechanical properties. Abstract : Organisms can synthesize heterogeneous structures with excellent mechanical properties through mineralization, the most typical of which are teeth. The tooth is an extraordinarily resilient bi-layered material that is composed of external enamel perpendicular to the tooth surface and internal dentin parallel to the tooth surface. The synthesis of enamel-like heterostructures with good mechanical properties remains an elusive challenge. In this study, we applied a biomimetic mineralization method to grow fluorapatite/CaCO3 (FAP/CaCO3 ) heterogeneous structured thin films that mimic their biogenic counterparts found in teeth through a three-step pathway: coating a polymer substrate, growing a layered calcite film, and mineralization of a fluorapatite columnar array on the calcite layer. The synthetic heterostructure composites combine well and exhibit good mechanical properties comparable to their biogenic counterparts. The FAP/CaCO3 heterogeneous structured composite exhibits excellent mechanical properties, with a hardness and Young's modulus of 1.99 ± 0.02 GPa and 47.5 ± 0.6 GPa, respectively. This study provides a reasonable new idea for unique heterogeneous structured materials designed at room temperature.